L'histoire immobile? Six centuries of real wages in France from Louis IX to Napoleon III : 1250-1860 - Leonardo Ridolfi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
This paper presents new series of real wages for male farmers and construction workers in France from 1250 to 1860. Between the first half of the thirteenth century and the mid-nineteenth century real wages displayed no substantial trend improvement. Even in the post-Black Death period, after a sharp temporary rise in real wages, there are few traces of a French "golden age" of labour especially during the worst phases of the Hundred Years War. In addition, consistently with the Malthusian interpretation, we find evidence of a long lasting inverse relationship between real wages and population.
Keywords: I30; J3; N33; O10; 330; Real wages; Living standards; France